TOEIC PREDICTION TEST AS A MEASUREMENT OF ENGLISH LANGUAGE ABILITY OF VOCATIONAL SCHOOL STUDENTS: A STUDY OF GRADE X STUDENTS OF SMKN 21 JAKARTA - Redjeki Agoestyowati; Umi Hani Makmuroh (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to analyze the results of the TOEIC Prediction Test as a tool to measure the English language proficiency of vocational high school (SMK) students, specifically tenth-grade students of SMKN 21 Jakarta. The study used a quantitative descriptive approach with 177 students from four majors: Accounting and Institutional Finance (AKL), Retail Business (BR), Office Management and Business Services (MPLB), and Software and Game Development (PPLG). Data were obtained from the TOEIC Prediction Test results on October 17, 2025, covering Listening, Reading, and total scores. The results showed that the average TOEIC Prediction score for students fell within the basic to intermediate range, with the PPLG major achieving the highest average score compared to other majors. These findings suggest that the TOEIC Prediction Test can be used as a tool for initial mapping of vocational high school students' English language proficiency. The results are expected to serve as a basis for planning more contextual English language learning that aligns with the needs of the workplace.